AB0606 LONG-TERM BIOLOGICAL TREATMENT IN LARGE VESSELS VASCULITIS: A RETROSPECTIVE SINGLE-CENTER STUDY ON 30 PATIENTS FROM 2011 TO 2018. (June 2019) - Regola, Francesca; Bosio, Giovanni; Cerudelli, Elisabetta; Tincani, Angela; Toniati, Paola
Abstract : Background: Glucocorticoids (GC) are the mainstay in the treatment of large vessels vasculitis (LVV), while conventional immunosuppressants have modest GC-sparing effect. Recent studies show that biological drugs could represent a valid therapeutic option, especially in patients with severe and/or relapsing LVV. Their role in the treatment of LVV is expanding, but only few data are available on their long-term efficacy and safety [1, 2]. Objectives: Our aim is to describe the 8 years' experience of a single Italian center in biological treatment of patients with large vessels vasculitis (LVV). Methods: We collected retrospectively clinical data from 30 patients affected by LVV and treated with biological drugs. Data from 18F-FDG PET and CT or MRI associated with improvement of clinical and inflammatory index (ESR and CRP) were used as criteria of response to treatment. Results: Between 2011 and 2018 we treated 30 LVV patients (22 women and 8 men) with biological drugs: 10 patients with Takayasu arteritis (TAK), 17 patients with large-vessel giant cell arteritis (LV-GCA) and 3 patients with aortitis. The median age (10 th –90 th percentile) at the diagnosis was 63 (21-79) years. Biological treatment was started right after the diagnosis in 15 patients, while 15 patients had a long-standing relapsed disease (time between diagnosis and biological therapy 6 (1-43) months). The mean follow-up time of patients was 26 (4-72) months. Anti-TNF-α drugs (infliximab, adalimumab, golimumab) were used in 9 patients; while anti-IL6r (tocilizumab) was used in 30 patients. During the follow up, 9 patients (23%) switched to another biologic for relapse of the disease or for infusive adverse reactions; in 3 cases multiple switches were made. Infliximab (IFX) was used in 7 patients for a median period of 12 (3-33) months: 3 patients archived stable remission, 3 had an infusive adverse reaction, 1 had a relapse of the disease after 60 months of therapy. Adalimumab (ADA) was used in 3 patients and then suspended in all of them for relapse of the disease after 3, 12 and 93 months of therapy, respectively. Golimumab was used in 2 patients: one suspended therapy for developing follicular thyroid cancer, one switched to another biologic for persistent active disease. Tocilizumab (TCZ) was used in all 30 patients for a median period of 20 (4-54) months: in 25 cases it was the first line therapy, in the other 5 cases it was used after an anti-TNF-α drug. 25 patients out of 30 (84%) archived stable remission and in 6 of them a dose tapering was possible, with no sign of relapse. Three patients in TCZ had an adverse reaction; one developed a uveitis and one had a relapse of TAK. In our last examination 29 out of 30 patients in biological therapy demonstrated a good control of the disease with clinical improvement, also confirmed by PET, TC and/or MRI, and reduction of inflammatory index (ESR and CRP), compared to before starting treatment. Biologics also demonstrated an important steroid sparing effect: mean prednisone dose at the beginning of treatment was 25 mg/day (12-50), while at the last follow-up was 6 mg/day (1-15) (p<0.0001; Wilcoxon test) Conclusion: In our cohort of 30 patients biological treatments demonstrated long-term efficacy and acceptable safety profile and important steroid sparing effect. References: [1] Pazzola G, et al. Rev Med interne, 2016 [2] Samson M, et al. Eur J intern Med, 2018 Disclosure of interests: Francesca Regola: None declared, Giovanni Bosio: None declared, Elisabetta Cerudelli: None declared, angela Tincani Consultant for: UCB, Pfizer, abbvie, BMS, Sanofi, Roche, GSK, alphaSigma, Lillly, Jannsen, Cellgene, Novartis, Paola Toniati: None declared